IL-14α as a Putative Biomarker for Stratification of Dry Eye in Primary Sjögren’s Syndrome - Liang, Yichen; Xian, Zhenhua; Fu, Dehua; Liu, Shuang; Yao, Yang; Jin, Yuebo; Gao, Chun; Shen, Long; Shi, Guixiu; He, Jing (Frontiers in Immunology, 2021)
Background: Dry eye is often the first presenting manifestation of primary Sjögren’s syndrome (pSS). Because of the high prevalence of dry eye disease in normal population, ophthalmologists urgently need a non-invasive and reliable screening test to diagnose dry eye associated SS patients, other than ocular symptoms and signs. Currently, there is no single test available. The correlation of serum IL-14α with pSS has been found in pSS mouse model. Purpose: To evaluate whether IL-14α can serve as a biomarker to stratify dry eye in primary Sjögren’s syndrome and its correlation to BAFF in a cohort of patients with non-SS dry eye (NSDE), pSS with dry eye disease, rheumatoid arthritis (RA), and healthy controls (HC). Methods: Retrospective study based on serum levels of IL-14α (defined by Western Blot) and BAFF (measured by ELISA) were evaluated among pSS with dry eye disease, NSDE, RA, and HC groups. Serum levels of SS related autoantibodies (Ro, La, SP1, PSP, and CA6) were also measured by ELISA. Results: One hundred and eighty patients were included for the current study, patients were separated into four groups as defined by pSS (n=65), NSDE (n=20), RA (n=50) and HC (n=45). The level of serum IL-14α in pSS was significantly higher compared to NSDE, RA, and HC (p=0.0011, p=0.0052 and p<0.0001, respectively). The levels of serum BAFF in pSS was significantly higher than in NSDE and HC (p=0.0148 and p<0.0001, respectively, whereas the levels of serum BAFF in RA was only significantly higher than in HC (p=0.001), but the level of BAFF was no significant difference between pSS and RA. In pSS, there was a decrease in the serum levels of IL-14α associated with a longer duration of the disease. Also, there was a correlation between the serum levels of IL-14α and SS related autoantibodies such as anti-SSA/Ro and anti-SSB/La in pSS patients. Conclusions: This is the first paper to report both IL-14α and BAFF could serve as a critical cytokine biomarker for the stratification of dry eye in primary Sjögren’s syndrome. This may help ophthalmologists to develop non-invasive metrics for the diagnosis of dry eye associated pSS.